Rational distribution of energy of probing radiation in the observation space of the hydrometeorological monitoring system - Perelygin, B.V. (Radiotekhnika, 2018)
The results of investigations are presented, which made it possible to reveal the most rational way of distributing the energy of probing radiation in the observation space. This method consists in the fact that the radars forming the field are placed at the vertices of the connected regular hexagons so that the observation zones of adjacent radars are superimposed on each other up to the full range of the radar, while limiting the elevation of the antenna patterns by the elevation angle. In this case, the absence of the need for energy distribution at large elevation angles creates a significant saving in the energy of the probing radiation and brings the degree of completeness of utilization of the radiation energy to 70%.